A população negra nos livros didáticos de biologia: uma análise afrocentrada por uma educação antirracista - Soares, Karina Maria de Souza (2020)
Brazil stands out as one of the largest multiracial populations in the world and is home to a significant contingent of African descendants dispersed throughout the diaspora, as well as being the scene of great socio-racial inequalities that persist in different spheres of society, especially in education. It is a nation resulting from a historical process formed on the basis of slavery and with detrimental consequences for the black population. Recognizing these injustices and the way they were structured allows for a critical look by educators in the development of meaningful strategies in favor of a non-hierarchical education that respects and celebrates the variety of cultural perspectives existing in the school community. This thesis presents a new concept of discussion for the contents present in high school biology textbooks as a proposal to promote an anti-racist education based on the epistemological principles of the Afrocentricity Theory. The problematization led us to ask: Do the high school biology textbooks contemplate problems related to the black population in order to allow these people to be understood in their historicity, culture and social and economic ways of life? The general objective was to analyze in the Biology textbooks approximations and distances between the narratives about the black population and the Afrocentricity paradigm. The specific objectives were: to analyze in the Biology textbooks the relationship between the narratives about the black people and education for ethnic-racial relations; investigate the commitment to the lexicon in the fight against linguistic racism in Biology textbooks; and, finally, to interpret imprints of the Eurocentric speech in secondary education Biology textbooks. The research was based on the qualitative approach and the bibliographic methodological procedures adopted, as an epistemological proposal for analysis of the collected data, the Theory of Afrocentricity built on its analytical categories, found on the contribution of theorists and researchers, such as Asante (2003; 2009 ; 2019), Karenga (2009), Diop (2010), Munanga (2004; 2012; 2019), Mazama (2009), Finch III (2009), Rabaka (2009), Nascimento (2009; 2014), among others. The results showed that the two didactic collections selected by PNLD 2018 (Textbook National Program), which are the most adopted by public secondary schools and that constituted our empirical field of investigation, diverge in the discussion of the ethnic-racial theme in the didactic contents. In the “Modern Biology” collection, the Eurocentric, racist, objective and uncritical character is highlighted in the approach to knowledge that distances it from Afrocentric principles. In the “Biology Today” collection, it is observed that the approximations in relation to the Afrocentricity paradigm are present, however in an occasional way. The fragility that is still present in these pedagogical materials is noted with regard to an approach that contemplates the various social groups as significant for the construction of knowledge, as well as the limits of the textbook evaluation programs by the Brazilian government in relation to the lack of consistency with what is recommended in their selection notices. Thus, it is concluded, that the Afrocentric idea for education, as an innovative counterhegemonic epistemological proposal, offers the black community the centrality of its history, science and culture in the approach of biological knowledge.